Trade policy in the BRIICS: A crisis stocktake and looking ahead - Razeen Sally (European Centre for International Political Economy (ECIPE), 2009)
The BRIICS - Brazil, Russia, India, Indonesia, China and South Africa - are the largest developing countries in their respective regions. A snapshot of their trade policies shows they have already liberalised trade and foreign direct investment extensively, and thereby plugged themselves into globalisation. This has helped to deliver higher growth, poverty reduction and improvements in human welfare. But external liberalisation has stalled. Creeping protectionism has set in. It has accelerated in the wake of the global economic crisis, generally translating into behind-the-border regulatory barriers emerging from domestic "crisis interventions". The BRIICS should have the following trade-policy priorities. First, in the short-term, they should counter creeping, crisis-related protectionism by containing the expansion of government at home. Second, looking beyond the immediate crisis, they should couple further trade and FDI liberalisation with behind-the-border regulatory reforms to improve the domestic business climate. Third, second-generation reforms are overwhelmingly domestic in nature. They should be done unilaterally, with less reliance on trade negotiations through the WTO and FTAs - not to mention the G20 and other "global-governance" paraphernalia. Fourth, unilateral reforms should be locked in through stronger WTO commitments, which should emerge from a post-Doha rule-improving agenda. Fifth, the BRIICS should exercise caution with "trade-light" FTAs. And sixth, all BRIICS need more trade-policy transparency. "Transparency boards", inside and outside government, should conduct and disseminate detailed analysis of the costs and benefits of trade policies in order to facilitate better deliberation of policy choices.
Keywords: 330; Internationale Handelspolitik; Außenwirtschaftspolitik; Auslandsinvestition; Protektionismus; Brasilien; China; Indien; Indonesien; Russland; Südafrika